Integrating Life Skills into the Curriculum to Enhance Student Well-Being at SMP Alam Balikpapan - Winarni Winarni; Dian Hidayati; Muhammad Zuhaery (Journal of Indonesian Progressive Education, 2026)
Student well-being has recently received serious attention from the government, as reflected in the policy of providing free nutritious meals. This study aims to examine the extent to which life skills embedded in the curriculum contribute to improving student wellbeing. The research employed a qualitative case study approach involving one principal, one teacher, and two eighth-grade students as participants. Data were collected through observation, interviews, and document analysis, while data validity was ensured through triangulation of data sources and research techniques. The findings indicate that the principal of SMP Alam Balikpapan plays a crucial role not only as an administrative manager but also as a visionary leader who directs school policies and culture toward strengthening life skills and student wellbeing. The principal actively integrates life skills into the curriculum, promotes experiential learning, and creates a safe learning environment that supports students’ social and emotional development. This role is reinforced through collaboration with teachers and support for instructional innovation. The implementation of contextual learning through outdoor activities and real-world projects has been shown to enhance students’ independence, responsibility, leadership, cooperation, and self-regulation, leading to increased self-confidence, resilience, and positive social relationships as key components of student wellbeing.